Antimicrobial use in breeding kennels and antimicrobial resistance profile of Escherichia coli and Staphylococcus pseudintermedius isolated from healthy breeding bitches in Northern Italy - Milani, Chiara; Diana, Alice; Corrò, Michela; Spagnolo, Elena; Del Carro, Angela; Rota, Ada; Bertero, Alessia (Frontiers in Veterinary Science, 2026)
Antimicrobials can be overused in dog breeding facilities, leading to increased resistance among commensal bacteria. The aim of this study was to investigate antimicrobial use intensity in a professional canine reproduction setting by assessing the resistance profiles of Escherichia coli and Staphylococcus pseudintermedius isolated from healthy breeding bitches, as well as through a questionnaire for breeders. Five bitches from each of 15 kennels in Northern Italy were sampled from the perivulvar skin and rectum, and the susceptibility of the isolated bacteria to a panel of different antimicrobials was determined (Minimum Inhibitory Concentration). Kennels were classified according to their reported intensity of antimicrobial use, and the association between antimicrobial use and resistance in S. pseudintermedius and E. coli was evaluated using Fisher’s exact test (p < 0.05). E. coli exhibited the highest resistance to ampicillin (around 50%), moderate resistance to amoxicillin-clavulanic acid (~24%) and cefalexin (~47%), while resistance to the remaining agents was low (generally ≤10–15%); the prevalence of Extended Spectrum Beta-Lactamase (ESBL)-producing E. coli was 7.76%. More than 82% of S. pseudintermedius strains were resistant to penicillin and ampicillin; mecA-positive methicillin-resistant S. pseudintermedius accounted for 17.65%. Multi-drug resistant (MDR, i.e., acquired non-susceptibility to at least one agent in three or more antimicrobial categories) E. coli and S. pseudintermedius were 22.53 and 41.18%, respectively. MDR E. coli were significantly more frequent in kennels reporting ‘high antimicrobial use’ (p = 0.0160). The generally high levels of acquired resistance suggest extensive antimicrobial use, especially beta-lactams. Breeder responses were partly inconsistent, indicating that complementary strategies should be adopted to monitor antimicrobial use in dog breeding facilities.